The Meaning Of Digital Balance And Employee Psychological Well-Being In The Era Of Work-Life Integration - Djuanda, Ade (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2025)
This study aims to reconstruct the essential meaning of Digital Boundary Management (DBM) and analyze its association with Eudaimonic Psychological Well-being (PWB) among Generation Z employees in Indonesian startup companies. The paradigm shift from Work-Life Balance (WLB) to Work-Life Integration (WLI), mediated by digital connectivity, has blurred professional and personal boundaries, giving rise to the risk of technostress.1 Using a qualitative, interpretive phenomenological approach, this study involved in-depth interviews with Gen Z employees working in a flexible startup environment. Data analysis follows the Colaizzi Method to uncover subjective experiences and the essence of meaning.2 The findings suggest that Digital Balance for Gen Z is a negotiative experience characterized by tension between individual efforts to uphold Digital Autonomy and collective pressures triggered by the internalization of the value of Digital Gotong Royong.3 The success of DBM is not measured by time separation, but by the extent to which intensive integration (WLI) can be justified by Purpose in Life and Personal Growth (Ryff's PWB dimensions).4 This study provides theoretical contributions by integrating cultural factors into Digital Boundary Theory and suggesting managerial implications, such as structurally supported Right to Disconnect policies, to maintain PWB in an integration-dominated work environment.